CHINESE POVERTY REDUCTION MODEL: A VIRILE TOOL FOR ACHIEVING POVERTY REDUCTION IN NIGERIA BY 2030 - Omotayo Vincent Adewale; Adewole Joseph Adeyinka; Ogunlokun Ayodele Damilola (Universitas Jember, 2023)
Various strategies have been used by Nigerian government in a bid to stem the tide of rising poverty in the country but poverty appears not to have been abated judging from the available statistics. However, China has been able to reduce its poverty from 57% to less than 1% between 1999 and 2020. Therefore, this study appraised empirically the efficacy of Chinese poverty reduction model reducing poverty in Nigeria. Both the CBN Statistical Bulletin and World Bank Development Indicators were used as sources for the data. The data were analyzed using regression utilizing the Ordinary Least Square method. The results showed that agricultural productivity, a component of China's strategy to combat poverty, had a significant impact on reducing poverty in Nigeria. Additionally, it was discovered that government spending on social services, another Chinese strategy, had a beneficial effect on the eradication of poverty. It was discovered that a 1% increase in the amount spent on social and community services in Nigeria resulted in a 21% decline in the country's poverty rate. However, it was found that agricultural spending was inversely correlated with capital income, which went against the theoretical prediction. Therefore, it was determined that the Chinese model for decreasing poverty, which incorporates better agricultural techniques, higher social security, and community services, will be effective in significantly lowering poverty in Nigeria by 2030.Keywords: Poverty Reduction, Chinese Model, Agricultural Productivity, Social and Community Expenditure